Application of fuzzy mathematics for choosing maintenance intervals for non-public railway tracks (Nexo Revista Científica, 2021)
This article discusses the application of fuzzy mathematics for choosing time windows for the maintenance of non-public railway tracks. The design features of several stations and the points of junction of non-public railway tracks lead to hostile routes in the leads of the station. Moving the switching fleet through the neck creates hostility to the train route. To determine the optimal maintenance interval of non-public railway tracks, aimed at excluding hostility, it is necessary to know the throughput reserve of the railroad neck element in a certain time window. To localize the throughput reserve, it is proposed to divide the day into 30-minute intervals. This division will allow determining more accurately both the throughput reserve of the railroad neck element and the periods for servicing non-public railway tracks. The most appropriate way to calculate the throughput reserve is to use fuzzy numbers since this method allows taking into account the unequal capabilities of values within the intervals. Using the defuzzification procedure, a natural number is assigned to a given fuzzy number. After carrying out the defuzzification of the throughput reserve, the obtained values can be used to build an algorithm for selecting service intervals for non-public railway tracks.